Biodegradability enhancement of hydrolyzed polyacrylamide wastewater by a combined Fenton-SBR treatment process. (April 2019) - Zhang, Lei; Su, Fei; Wang, Nan; Liu, Shuai; Yang, Mei; Wang, Yong-Zhong; Huo, Danqun; Zhao, Tiantao
Graphical abstract: Highlights: Fenton-SBR process was applied to treat HPAM-containing drilling wastewater. COD, HPAM, NH4 + -N, and TP in raw and treated wastewater were effectively removal. The maximal COD and HPAM removal efficiencies were 98.35% and 87.58%. HPAM structure analysis was performed using FT-IR and UV spectroscopy. Functional microorganisms was determined by Illumina MiSeq Sequencing. Abstract: An efficient way to solve the environmental pollution deriving from hydrolyzed polyacrylamide (HPAM)-containing drilling wastewater is urgent. This work adopted a novel method coupling Fenton oxidation with sequencing batch reactor (SBR) to treat gas-field drilling wastewater successively. This Fenton-SBR process reduced COD, HPAM, NH4 + -N and total phosphorus (TP) concentrations of drilling wastewater by 98.35%, 87.58%, 94.50% and 93.52%, respectively. While simulated HPAM wastewater with similar HPAM concentration to Fenton-oxidized drilling wastewater was treated only by biological process, and the COD and HPAM removal efficiencies reached 78.26% and 62.95%. The result indicates that the biodegradability of the drilling wastewater was enhanced after Fenton oxidation. Moreover, the analysis on microbial community structure indicates the dominant bacteria in treated drilling wastewater were different from that in treated simulated-wastewater. It can be considered the Fenton-SBR process possesses potential to be applied to treating the drilling wastewater.